Pengaruh Orang Tua dalam Membentuk Karakter Religius Siswa Kelas IV-VI di Madrasah Ibtidaiyah Baitul Huda Pucangro Kecamatan Gudo Kabupaten Jombang - Pahlawati, Eny Fatimatuszuhro; Sakina, Bella Intan; Muhtadi, Muhtadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT In the context of education, parents serve not only as providers of physical needs but also as primary educators responsible for instilling religious and moral values ​​in their children. This study aims to determine the influence of parents in shaping the religious character of students at Baitul Huda Pucangro Elementary School, Gudo District, Jombang Regency. The research method used was quantitative, with data collection techniques through observation, interviews, documentation, and questionnaires distributed to 40 respondents, students in grades IV-VI. Data analysis used a statistically based product-moment correlation technique. The results showed that parents have a significant influence on the formation of students' religious character, with a correlation coefficient of 0.6008. Students who receive attention and guidance from their parents demonstrate better religious understanding, attitudes, and behavior compared to students who receive less such support. Keywords: Parents, Religious Character, Students